Implementasi Metode Pose to Pose dalam Perancangan Ekspresi dan Gestur Pada Karakter Deka dan Dara dari Animasi 3D Ficusia - Shabiratin, Azmah; Mulia, Mariska; Wahyudi, Afdhol (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2025)
As technology builds up, the multimedia process is also evolving. Animation is one of the entertainment media that people of all ages enjoy. All of them appreciate animation. One of the issues that occurs in animating is the expression and gestures that aren't strong enough. An animation's message and atmosphere can be conveyed through these two elements. One technique animators can use is called the pose to pose method. The purpose of this paper is to describe the expressions and gestures process of characters from the 3D Animation Series Ficusia using the pose to pose method. Two characters from this animation were used to compose this research by setting the keyframe to identify the key pose, timing, and spacing, and considering the total number of frames used. This research was conducted using Blender.